III-V/Si device modeling and circuit simulation - Xu, Haoying (Nanyang Technological University, 2020)
The demand for high performance power electronics devices in electric vehicle, aerospace engineering, and renewable energy is increasing. Traditional silicon-based power devices are reaching their upper performance limit and fail to meet the requirements for higher switching frequency, power efficiency, and operating temperatures. Thus, power electronics industries have to explore for potential semiconductor materials whose performance can match today’s new systems. One of the potential materials is gallium nitride (GaN).